(untitled) (Discourse of Law and Administration, 2023)
What’s the rule of law from the French point of view and why is it currently going through a crisis? Those two questions are analyzed in this contribution. This shows that even in the country of the Declaration of human and civic rights, the State can be arbitrary, especially during times of crisis. T hat study is about researching the place of France in the crisis of the rule of law in the European Union, in general, and in the management of the COVID-19 pandemic, in a more specific way. The way in which national authorities manage crises is worrying, while the rule of law is already threatened by a very tense European context